EVALUASI PELAKSANAAN PHBM DALAM UPAYA PELESTARIAN HUTAN PRODUKSI DI BKPH PURWOREJO KPH KEDU SELATAN (Studi Kasus Hutan BKPH Purworejo) - , Sajiman, Dr. Erny Poedjirahajoe, MP ([Yogyakarta] : Universitas Gadjah Mada, 2012)
The reseach was conducted to evaluate the implementation of Pengelolaan Hutan Bersama Masyarakat (PHBM) in Bagian Kesatuan Pemangkuan Hutan (BKPH) Purworejo, Kesatuan Pemangkuan Hutan (KPH) South Kedu, Perum Perhutani Unit I Central Java. This research is located in the Sedayu Village, subdistrict Loano, Purworejo regency. This village was chosen because it has the bosom of wengkon or Hutan Pangkuan Desa (HPD) which is managed by Lembaga Masyarakat Desa Hutan (LMDH) Sedya Rahayu. HPD isused as the implementation of PHBM is administratively located in Resort Pemangkuan Hutan (RPH) Loano dan RPH Katerban, BKPH Purworejo, KPH South Kedu. This study aims to determine the implementation of PHBM, efforts made by LMDH in the region, the impact of PHBM implementation and evaluation of PHBM implementation in the region. Evaluation is done by using a standard evaluation set forth in the Decree Number of Directors Perhutani office 660/Kpts/Dir/2003 on Guide lines for Evaluation of Pengelolaan Hutan Bersama Masyarakat. The results showed that the implementation process begins with the socialization of PHBM, multi-agreement, participatory planning as well. The efforts made by LMDH Sedya Rahayu in the PHBM implementation seeks pine sap collection, culvitation under standing and participation in forest protection. The impact of PHBM people's income to be increased because of revenue sharing of forest in the village. The result of the evaluation of the PHBM implementation in the research area shows the value of the criterion well, so it is suggested that PHBM program continues to be implemented is still being done intensive coaching and mentoring of The Manager (Perhutani) and Administrator LMDH.